Effect of electrostatic interactions and complexes formation between nisin and bacterial exopolysaccharides on nisin antimicrobial efficacy. (May 2021) - Abid, Yousra; Ben Amara, Chedia; Gharsallah, Houda; Dumas, Emilie; Chihib, Nour-Eddine; Attia, Hamadi; Azabou, Samia; Gharsallaoui, Adem
Abstract: This study aims to describe interactions that may occur between nisin and bacterial exopolysaccharides (EPS) when they are present together in a model solution. For this purpose, two EPS, namely EPS-GM and EPS-BMS, produced by potential probiotic Bacillus tequilensis -GM and Leuconostoc citreum -BMS, respectively, were used. Results showed that maximal complexation occurred at pH 5.0 between anionic EPS (1.5 g/L) and cationic nisin (1 g/L) mainly through electrostatic interactions. Results provided by scanning electron microscopy, epifluorescence microscopy and turbidity measurements showed that EPS-GM was able to form bigger and higher amounts of complexes with nisin. The nisin antimicrobial activity was interestingly not affected and even improved after its complexation with EPS suggesting that these latter may act as protective agents of the nisin antimicrobial activity when applied in foods. The results of this study should help food technologists to optimize the physicochemical conditions for optimal formulation of food products containing EPS. Highlights: Interactions between nisin and bacterial exopolysaccharides were studied. Complexation occurred mainly through electrostatic interactions. Maximal complexation occurred at pH 5.0 with 1.5 g/L of EPS and 1 g/L of nisin. Complexation did not affect nisin antimicrobial activity.